(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Violence against children and adolescents is harmful and may intensify social, emotional, psychological, and cognitive impacts throughout the life course. Objective: To analyze the existing literature on the impacts of child violence and positive parenting as an alternative to violent educational practices. Methods: A narrative literature review was conducted through searches on the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), and Google Scholar platforms, using the keywords positive parenting, child protection, child violence, as well as the terms “Lei Menino Bernardo” and Law 14.826/2024, focusing on the last ten years. Results: Six studies were selected, indicating that physical violence against children in Brazil, intended to punish or suppress behaviors remains an alarming reality. The studies show that violent educational practices may result in long-lasting harm and increase the risk of developing psychopathologies. Despite current legislation, such as the Statute of the Child and Adolescent and regulatory frameworks promoting positive parenting, cultural acceptance of physical punishment continues to be a barrier to overcoming such practices, highlighting the need for stronger public policy action. Conclusion: The training and capacity-building of professionals working in the protection network are essential measures to transform paradigms and consolidate practices that prioritize care, respect, and the holistic development of children, in accordance with the law.